CL!C, uma newsletter sobre criatividade - Moreira, Filippe Luy dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The CL!C project is a digital newsletter that explores creativity as an essential tool in everyday life and several professional fields, including journalism. The newsletter discusses how creativity can be applied in practical and innovative ways through interviews, reports, and curated content. The objective is to investigate and illustrate different forms of creativity, offering a multiplatform, visually appealing, and hypermedia journalistic product aimed at Generation Z and professionals in the creative industry.

O projeto CL!C é uma newsletter digital que explora a criatividade como uma ferramenta essencial no cotidiano e em diversos campos profissionais, incluindo o jornalismo. A newsletter aborda como a criatividade pode ser aplicada de maneira prática e inovadora, utilizando entrevistas, reportagens e curadoria de conteúdo. O objetivo é investigar e ilustrar as diversas formas de criatividade, oferecendo um produto jornalístico multiplataforma, visualmente atrativo e hipermidiático, voltado para a geração Z e profissionais da área criativa.
CL!C, a newsletter about creativity
Keywords: Criatividade; Jornalismo digital; Newsletters; Webjornalismo; Creativity; Digital journalism; Web journalism; Newsletter journalism